Determinan Keluhan Penyakit Kulit pada Pemulung di Tempat Pembuangan Akhir - Dini Daningrum; Dika Sulastri; Tika Yuliana; Maman Sutisna; Etty Nurkhayati (Faletehan Health Journal, 2022)
Scavengers are people or independent informal workers who take unused items, such as plastics, cardboards and irons that can be sold and recycled. The risk of disease transmission to scavengers is greater because their work directly relates to wastes. Environmental-based diseases might be skin disorders caused by bacteria, viruses and fungi. The purpose of this study was to determine the factors associated with skin complaints of scavengers in final disposal site. The research design used was cross-sectional. The population of this study were all scavengers at Bangkonol Final Disposal Site, Pandeglang Regency. The sample of this study amounted to 120 scavengers taken by total sampling. The results showed that there was a relationship between personal hygiene (Pv = 0.000), knowledge (Pv = 0.000), availability of information (Pv = 0.000), and working period (Pv = 0.000) with skin disease complaints. Meanwhile, there was no relationship between length of contact (Pv = 0.521) and complaints of skin diseases. Scavengers should pay more attention to clean and healthy living behaviors, including washing hands after and before work, bathing twice a day, cutting nails regularly (once a week), and regularly changing work clothes daily.